The Psychological Underpinnings of Beliefs in Amulets and Dependence on Monks in Buddhism: An Examination of Their Social Roles in Thai Society - Singson, Sreepanja; Phayaphrom, Bordin; Chongkumnungsil, Wuttichai; Nurittamont, Wasutida (Journal of Posthumanism, 2025)
Belief in amulets and monks is deeply rooted in Thai culture and daily life, often serving as psychological tools to cope with uncertainty and stress. Although widespread, psychological studies on the underlying mechanisms of such beliefs remain scarce. This study aims to explore personal and social well-being, values, and attitudes behind these beliefs in the Thai sociocultural context, including both believers and non-believers. Data were collected through semi-structured interviews with 24 participants and expanded via purposive sampling. Interpretative Phenomenological Analysis (IPA) and Insight7 were used to uncover deeper meanings. Findings indicate that psychological needs, such as the desire for reassurance, significantly influence belief in amulets. Participants showed a negotiation between traditional Buddhist values and modern societal demands, with amulets and monks acting as coping mechanisms. The study reveals complex links between psychology, religion, and culture, offering insights into belief systems across Southeast Asia.